Evaluation and Management of Symptomatic Vasospasm following Endoscopic Endonasal Resection of Pediatric Adamantinomatous Craniopharyngioma - Dustin Hansen; Joaquin Hidalgo; Alan Cohen; Debraj Mukherjee; Susanna Scafidi (Case Reports in Pediatrics)
Background. Cerebral vasospasm is a well-described pathology following subarachnoid hemorrhage and trauma in children; however, very few cases have been published following craniopharyngioma resection in children. Those that were published were associated with significant morbidity or mortality at hospital discharge. Case Summary. Here, we report the challenging clinical course of a pediatric patient who developed delayed cerebral vasospasm following craniopharyngioma resection. It was first noted on postoperative day 13. The patient was managed with induced hypertension, hypervolemia, and intra-arterial vasodilator therapy (nicardipine). This patient made a full recovery without new focal deficits at hospital discharge. Conclusion. In contrast to previously reported similar pediatric cases, this patient with cerebral vasospasm after craniopharyngioma resection made a full recovery without new focal neurologic deficits. To our knowledge, this is the first occurrence of a patient with this clinical course.